PEMANFAATAN BALAI DUSUN SEBAGAI RUANG BACA DESA UNTUK ANAK USIA SEKOLAH DI DESA TAWANGREJO - Aliyah, Himatul; Akhmad, Fauzi; Fina Surya, Anggraini (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
Drug abuse among teenagers is increasing. The rise of this behavioral deviation also occurs in Tawangrejo Village, especially among school-age children. This not only raises concerns, but can also threaten health, disrupt stability and endanger the sustainability of the nation’s generation. One of the preventive efforts that can be done is by providing alternative positive and productive activities such as reading rooms. This service focuses on utilizing the hamlet hall as a village reading room for school-age children. The service method used is the ABCD (Asset Based Community Development) approach which emphasizes community empowerment by utilizing and developing local assets in Tawangrejo Village to achieve common goals. The result of this service is the utilization of the hamlet hall as a comfortable and affordable reading room, so that children have better access to useful reading materials. The reading room is expected to increase children’s interest in reading and literacy skills, as well as become a safe and productive place that can have a positive impact on drug abuse prevention.